2002
DOI: 10.2337/diabetes.51.2007.s134
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxicity in Human Pancreatic Islets and the Protective Effect of Metformin

Abstract: Human pancreatic islets from eight donors were incubated for 48 h in the presence of 2.0 mmol/l free fatty acid (FFA) (oleate to palmitate, 2 to 1). Insulin secretion was then assessed in response to glucose (16.7 mmol/l), arginine (20 mmol/l), and glyburide (200 mol/l) during static incubation or by perifusion. Glucose oxidation and utilization and intra-islet triglyceride content were measured. The effect of metformin (2.4 g/ml) was studied because it protects rat islets from lipotoxicity. Glucose-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 26 publications
4
106
0
1
Order By: Relevance
“…2). Metformin could protect human pancreatic islets from the lipotoxicity (24,25). That early insulin treatment could protect b-cell function of LADA patients was also reported (26,27).…”
Section: Resultsmentioning
confidence: 94%
“…2). Metformin could protect human pancreatic islets from the lipotoxicity (24,25). That early insulin treatment could protect b-cell function of LADA patients was also reported (26,27).…”
Section: Resultsmentioning
confidence: 94%
“…In vitro studies suggest a directly protective effect of metformin on rat and human islets from glucotoxicity and lipotoxicity. 76,77 In the UKPDS, patients with newly diagnosed T2D who received metformin had an initial increase in beta-cell function (assessed by HOMA) in the first year, but this subsequently declined at a similar rate to those treated with diet or sulphonylureas despite persistently increased insulin sensitivity with metformin. 15 Similarly, the ADOPT (A Diabetes Outcome Progression Trial) study of recently diagnosed T2D patients showed a small early benefit of metformin on beta-cell function (in response to OGTT), followed by a slow decline -albeit less than those receiving sulphonylurea therapy -over four years.…”
Section: Metforminmentioning
confidence: 99%
“…4) Several studies have shown that biguanides are also effective at lowering blood sugar and that they preserve beta-cell function. [5][6][7][8] It was also shown that metformin may be associated with fewer DM-related adverse events compared with other antidiabetics, 9) although it is still controversial. However, phenformin, which was the only biguanide available in the United States, was withdrawn from the market in the late 1970s because it was found to be associated with lactic acidosis with a high fatality rate.…”
mentioning
confidence: 99%